Kontrol Edukasi Video Visual Smartphone Berbasis Selfcare terhadap Kecemasan dan Tekanan Darah Pasien Endoskopi dengan Pelayanan Anestesiologi (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effect of self-care-based smartphone visual video education on the anxiety level and blood pressure of endoscopic patients with anesthesiology services. This research method uses a quasy experiment (pre-post test with control group design). The results showed that there were differences between the treatment and control groups. There were significant differences in anxiety (p=0.000), systolic blood pressure (p=0.011), and diastolic blood pressure (p=0.042). In the intervention group, there was a significant effect of smartphone visual video education on anxiety (p=0.000), systolic blood pressure (0.042), and diastolic blood pressure (p=0.008). In conclusion, self-care-based smartphone graphic video education affects the anxiety and blood pressure of endoscopic patients with anesthesiology services.Keywords: Education, Endoscopy, Anxiety, Blood Pressure, Video